Efeitos da perda de peso r??pida sobre a contagem de leuc??citos, hidrata????o e for??a muscular em lutadores de artes marciais mistas - Camar??o, Nathalia Ferreira (2016)
MMA championships are bounded by weight category. Athletes re usually mantain bodyweight above the limit of category and pratice rapid wight loss for the weight-in moment, with subsequent weight regain until the moment of the combat. Therefore, the aim of this study was to investigate hidration status, immue parameters, and isometric strenght in professional MMA fighters who underwent smaller (group 1, n = 6) or greater (group 2, n = 6 ) rapid weight loss in two momwnts: at weigh-in and immediately prior to the competition. We used blood tests to quantify the total and differential leukocyte count,, handgrip strength test and verified variation among the usual weight and weight at the time of the fight. Groups were divided establishing percentile 50%, considering delta perceptual of weight loss from the usual weight and weigh-in weight. Even after verify normality of the sample distributionby the Shapiro-Wilk test, we decided to use non-parametric statistical analysis, given the fact the sample size. We used Mann-Whitney test to verify thedifference between groups and Wilcoxon test to verify the difference between moments. . Values are expressed as median, mean ?? standard deviation. The median and the average percentage of weight loss delta are statistically different between the groups (p???0,05). Group 1: median = 5.54, mean = 6.45 ?? 3.98%, and Group 2: median = 12, 99, mean = 14.23 ?? 2.52%. The groups are homogeneous in the following variables: age (Group 1: median = 22, mean = 26.5 ?? 11.30 years; Group 2: median = 27, mean = 27.5 ?? 2.35 years); height (Group 1: median 174.5, mean = 176.8 ?? 0.06 cm; Group 2: median = 176, mean = 177.2 ?? 0.04 cm); BMI (Group 1: median = 25.17, mean = 25.23 ?? 2.71 kg / m 2, Group 2: median = 25, 06, mean = 25.54 ?? 1.26 kg / m2) body weight (Group 1: median 78.5, mean = 78.67 ?? 6.15 kg; Group 2: median 79.0, mean = 80.17 ?? 4,83kg). Between groups, we observed total leukocytes decreased in Group 1 (median = 8850, 11450 = maximum value, minimum value = 4850, mean = 8408.44 ?? 2585.6 mm3) compared to Group 2 ( median = 8300, maximum = 17400, minimum value = 4200, mean = 9208.3 ?? 4732.1 mm3) at the of weigh-in, with statistically significant difference (p <0.05).No significant differences between groups and moments were found for neutrophils, lymphocytes and neutrophil/lymphocyte ratio. Furthermore, no significant differences were observed on absolute and relative isometric handgrip strength between groups and moments. In conclusion, greater rapid wight loss can transiently downregulate immune parameters. We elucidate the needin of rules to determinate maximum values of weight loss and regain prior to championships.